1988
DOI: 10.1002/ijc.2910410309
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and risk of cancer of the lower urinary tract among men. A case‐control study

Abstract: Data from a hospital-based matched case-control study with 531 male pairs were analyzed for risks of cancer of the lower urinary tract associated with previous employment and particular occupational exposures. Statistically significant odds ratios were obtained for ever-employment as mining workers (2.0), turners (2.3), tailors (2.7), truck drivers (1.8), locomotive drivers (3.0) and janitors (3.5), whereas odds ratios of 3.0 or more, found for rubber and plastics workers, printing workers, gas workers, artist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
58
1
6

Year Published

1992
1992
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 31 publications
5
58
1
6
Order By: Relevance
“…The SMR for each railway-related occupation was elevated: railway engine drivers (SMR,161), shunters (SMR,149), guards (SMR,258) signalmen (SMR,146) and lengthmen (SMR,147). Six recent case-control studies have presented data on bladder cancer risk among railway workers, five of which reported risk estimates above 1.0 (Howe et al, 1980;Silverman et al, 1983;Veneis & Magnani, 1985;Brownson et al, 1987;Claude et al, 1988;Risch et al, 1988). One cohort study of railway workers evaluated bladder cancer risk and found a relative risk of 1.0 (Howe et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The SMR for each railway-related occupation was elevated: railway engine drivers (SMR,161), shunters (SMR,149), guards (SMR,258) signalmen (SMR,146) and lengthmen (SMR,147). Six recent case-control studies have presented data on bladder cancer risk among railway workers, five of which reported risk estimates above 1.0 (Howe et al, 1980;Silverman et al, 1983;Veneis & Magnani, 1985;Brownson et al, 1987;Claude et al, 1988;Risch et al, 1988). One cohort study of railway workers evaluated bladder cancer risk and found a relative risk of 1.0 (Howe et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Seven case-control studies and one registry-linkage study have examined bladder cancer risk among electrical and electronic workers, of which four found at least a 20% excess of cases (Anthony & Thomas, 1970;Silverman et al, 1983;Baxter & McDowall, 1986;Coggon et al, 1986;Malker et al, 1987;Claude et al, 1988;Gonzalez et al, 1989;Schumacher et al, 1989). Steineck et al (1989) reported elevated risk for exposure to polychlorinated biphenyls (PCB).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For other occupations, available data are nonconclusive (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and thus deserve further attention (23). One of the limitations of most community-based studies conducted so far is that the prevalence of exposure in the textile industry has been relatively low, and therefore no detailed analysis of occupations and processes within this industry has been possible.…”
mentioning
confidence: 99%